2004
DOI: 10.1093/hmg/ddh180
|View full text |Cite
|
Sign up to set email alerts
|

Parkin protects human dopaminergic neuroblastoma cells against dopamine-induced apoptosis

Abstract: Parkinson's disease (PD) is characterized by the selective degeneration of dopaminergic (DA) neurons in substantia nigra pars compacta (SNpc). A combination of genetic and environmental factors contributes to such a specific loss. Among the five PD-linked genes identified so far, parkin, a protein-ubiquitin E3 ligase, appears to be the most prevalent genetic factor in PD. Although a variety of substrates have been identified for parkin, none of them is selectively expressed in nigral DA neurons. It remains unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
160
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(183 citation statements)
references
References 36 publications
21
160
2
Order By: Relevance
“…Parkin expression protects against caspase activation and cell death induced by stressors such as staurosporine, C2 ceramide, rotenone, and 6-OHDA (10,(12)(13)(14), and we extended these observations to include another stressor, etoposide. Neuronal dopaminergic MES and MES cells stably overexpressing human parkin (MES-Parkin) were treated with vehicle (DMSO) or etoposide (100 μM), and caspase 3/7 activity was measured at 18 h. Parental MES cells demonstrated a 100% increase in caspase 3/7 activity that was prevented by the stable over-expression of parkin (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Parkin expression protects against caspase activation and cell death induced by stressors such as staurosporine, C2 ceramide, rotenone, and 6-OHDA (10,(12)(13)(14), and we extended these observations to include another stressor, etoposide. Neuronal dopaminergic MES and MES cells stably overexpressing human parkin (MES-Parkin) were treated with vehicle (DMSO) or etoposide (100 μM), and caspase 3/7 activity was measured at 18 h. Parental MES cells demonstrated a 100% increase in caspase 3/7 activity that was prevented by the stable over-expression of parkin (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Our finding that altered GstS1 activity inf luences the parkin mutant phenotypes raises the possibility that parkin may also offer protection from the effects of oxidative stress. Further support for this hypothesis comes from the findings that oxidative damage in f lies, mice, and cell lines and sensitivity to oxidative stress agents in f lies and cell lines correlates inversely with parkin activity (19,(32)(33)(34). Our recent results from transcriptional profiling of parkin mutants and a genetic screen for parkin modifiers also demonstrate that oxidative stress response elements are up-regulated and that mutations in oxidative stress response components enhance the parkin mutant phenotypes (15).…”
Section: Discussionmentioning
confidence: 89%
“…Thus, abnormal ERK1/2 activation plays a critical role in PD pathogenesis. Parkin is documented to mediate neuroprotection against 6-OHDA-induced neurotoxicity [7,21,41,42] . As parkin is an E3 ubiquitin ligase, its neuroprotective effect may be executed via its substrates.…”
Section: Discussionmentioning
confidence: 99%
“…PARK2 mutations lead to the loss of its function and therefore to an accumulation of its substrates in the brain; such accumulation is related to the occurrence of PD [6] . It has been reported that parkin, but not its pathogenic mutants, can protect DA neurons against neurotoxicity [7] .…”
Section: Introductionmentioning
confidence: 99%